2013
DOI: 10.1590/s1677-5538.ibju.2013.03.03
|View full text |Cite
|
Sign up to set email alerts
|

High serum folate is associated with reduced biochemical recurrence after radical prostatectomy: Results from the SEARCH Database

Abstract: Introduction:To analyze the association between serum levels of folate and risk of biochemical recurrence after radical prostatectomy among men from the Shared Equal Access Regional Cancer Hospital (SEARCH) database. Materials and Methods: Retrospective analysis of 135 subjects from the SEARCH database treated between 1991-2009 with available preoperative serum folate levels. Patients' characteristics at the time of the surgery were analyzed with ranksum and linear regression. Uni-and multivariable analyses of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…Two meta-analyses also showed that circulating folate levels were positively associated with an increased risk of PCa [ 92 , 93 ], while dietary or supplemental folate had no effect on PCa risk [ 94 ] in a cohort study with 58,279 men in the Netherlands [ 95 ] and a case–control study in Italy and Switzerland [ 96 ]. In fact, one study of a cohort of men undergoing radical prostatectomy at several Veterans Administration facilities across the US even showed that higher serum folate levels were associated with lower PSA and, thus, lower risk for biochemical failure [ 97 ]. Another study using data from the 2007 to 2010 National Health and Nutrition Examination Survey showed that a higher folate status may be protective against elevated PSA levels among 3,293 men, 40-years old and older, without diagnosed PCa [ 98 ].…”
Section: Nutrientsmentioning
confidence: 99%
“…Two meta-analyses also showed that circulating folate levels were positively associated with an increased risk of PCa [ 92 , 93 ], while dietary or supplemental folate had no effect on PCa risk [ 94 ] in a cohort study with 58,279 men in the Netherlands [ 95 ] and a case–control study in Italy and Switzerland [ 96 ]. In fact, one study of a cohort of men undergoing radical prostatectomy at several Veterans Administration facilities across the US even showed that higher serum folate levels were associated with lower PSA and, thus, lower risk for biochemical failure [ 97 ]. Another study using data from the 2007 to 2010 National Health and Nutrition Examination Survey showed that a higher folate status may be protective against elevated PSA levels among 3,293 men, 40-years old and older, without diagnosed PCa [ 98 ].…”
Section: Nutrientsmentioning
confidence: 99%
“…); and that a diet high in folate (found in some fruits, beans and green vegetables) is associated with lower prostate cancer recurrence (Moreira et al . ). Moreover, the consumption of green tea, lycopene (found mainly in cooked tomatoes), omega‐3 fatty acids (found mainly in oily fish) and soya has also been linked to reductions in the risk of prostate cancer progression (Davies et al .…”
Section: Introductionmentioning
confidence: 97%
“…There are indications that dietary modifications after diagnosis can significantly decrease prostate-specific antigen (PSA) levels (the recurrence of the cancer is indicated by high PSA levels) (e.g. Dalais et al 2004); that a diet high in fat is associated with prostate cancer progression and mortality (Berkow et al 2007); and that a diet high in folate (found in some fruits, beans and green vegetables) is associated with lower prostate cancer recurrence (Moreira et al 2013). Moreover, the consumption of green tea, lycopene (found mainly in cooked tomatoes), omega-3 fatty acids (found mainly in oily fish) and soya has also been linked to reductions in the risk of prostate cancer progression (Davies et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This can explain why patients in the first study who rely on their doctor for advice were less likely to change their diet. GPs were also sceptical on the role of diet in prostate cancer after diagnosis even though benefits in prostate-specific antigen (PSA) levels (Dalais et al, 2004), mortality, progression (Berkow, Barnard, Saxe, & Ankerberg-Nobis, 2007) and recurrence (Moreira et al, 2013) are reported. Therefore, enhancing GPs' ability to provide dietary advice has the potential to benefit patients who rely on their advice while a need is reported to improve nutritional training in most of primary care colleges in Europe (Pineiro et al, 2005).…”
Section: Discussionmentioning
confidence: 99%